Optimalisasi Penanggulangan Stunting Melalui Sosialisasi Dan Pembagian PMT Di Posyandu Desa Tulung - Ayuk Permata Sari; Choirunnisa, Azizah; Fitria, Nurul; Styaningsih, Siti Nadia; Sasmita, Vina Dwi (Universitas Negeri Semarang, 2024)
Many people do not understand the importance of balanced nutrition in preventing and controlling stunting. Stunting is one of the problems in Tulung Village. One way to overcome stunting is through PMT (supplementary feeding) to meet the protein needs of babies and toddlers. The stages initiated by Unnes Giat 7 students were preparation, implementation and evaluation. In posyandu activities, students participate in registration, weighing, measuring, recording and distributing PMT. Inthis case, students designed a work program in the form of making PMTs, socializing the making of PMTs, and distributing PMTs to children who came to the posyandu in Dukuh Kiyaran. The socialization of making PMT by Unnes Giat 7 students provided an understanding of the processing of ingredients for PMT snacks. It is hoped that the activities programmed by Unnes Giat 7 students can be useful and optimize stunting prevention in Tulung Village.